Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


⇒ (x-1)³ = 2³
applying cube roots on both sides
⇒ ∛(x-1)³ = ∛2³
⇒ x-1=2
⇒ x=2+1
⇒ x=3

(x+1)² =?
put x=3 as we solved it above
    = 4²
    = 16.
(x+1)² =16

4 4 4
she explained it well
but sometimes if we use direct steps some users may not know how do we get that... So we have to provide our best to the users although it is simple or tough
(Y) ur ryt :p :)
:) thnk uu

This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
(x-1) = ∛8
x-1 = 2
x= 2+1
So, (x+1)² = (3+1)²
(4)² = 16

2 3 2
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts